Maternal deaths, near misses and great saves. Severe maternal outcome in Metro East, Western Cape Province, South Africa - Heitkamp, Anke (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.